THE PHENOMENON OF FREE DATING AFTER ENGAGEMENT: A REVIEW OF THE INTERPRETATION OF THE KHITBAH SHARIA IN THE QUR'AN - Munir, Muhammad Syamsul; Al Faruq, Abdul Qudus; Thobroni, Ahmad Yusam (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
The phenomenon of unrestricted dating after engagement has sparked a critical debate within Islamic thought concerning the enforcement of Sharia law. Society perceives dating after engagement as a means to better understand each other to prevent divorce, alongside the assumption that khitbah is considered a permissible form of dating. Based on this issue, the researcher aims to re-examine the interpretation of khitbah in the Qur'an. The method employed is qualitative, categorized under library research, utilizing documentation techniques with historical analysis. The findings of this study indicate that Islam encourages its followers to marry as a means of safeguarding themselves from sinful acts and fulfilling the principles of sunnatullah. Marriage in Islam is regarded as a form of worship aimed at creating a harmonious, loving, and respectful family. The practice of unrestricted dating after khitbah or engagement is seen as deviating from the Islamic purpose of marriage. Commitment to Sharia and adherence to religious boundaries are key in the process of establishing a legitimate relationship. Therefore, preserving honor and following religious guidance in premarital relationships represent a Muslim's responsibility in upholding Islamic values and Sharia law.